Recent advances in phytochemical-based Nano-formulation for drug-resistant Cancer - Mahesh P. More; Sagar R. Pardeshi; Chandrakantsing V. Pardeshi; Gaurav A. Sonawane; Mahesh N. Shinde; Prashant K. Deshmukh; Jitendra B. Naik; Abhijeet D. Kulkarni (Elsevier, 2021)
The graph of drug resistance in cancer is reportedly increasing in terms of therapeutic efficiency. As per the WHO reports, around 70% of death reported in low- and middle-income countries. The increase in death toll was imparted from improper diagnosis and inadequate therapy. The 25% increase in disease burden may be laden due to resistance mutations in cancer during treatment. Exposure of high concentrations of chemotherapeutic agents leads to toxicity in the normal cells. Long-term conventional chemotherapy develops acquired resistance. The conventional therapeutics was not able to target the cancer cell specifically and need to promulgate the use of nanocarrier or bioengineering for the polychemotherapy. Phytochemicals are natural constituents providing alternative therapeutic approach to minimize the resistance. The present review highlights the nano-therapeutic approaches pondering over the conventional chemotherapy. The phytochemicals are extracted, isolated, and purified from daily dietary fibers or natural plants. Natural extractives act via multiple pathways and provide optimum effectiveness against resistance cancer. The poor solubility and bioavailability are major constraints in combination therapy. The nanotechnological approach improves the functional properties transportation across cell barriers, and improves bioavailability. The present review highlights the phytochemical based nanoformulations in improving the therapeutic response and several alternative ways to target resistance cancer. The major implications of phytochemical and chemotherapeutic combination therapy could lead in the future.